Step-by-step Solution

Solve the equation with radicals $\sqrt{3t}-2=0$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

$\sqrt{3t}-2=0$

Learn how to solve equations with square roots problems step by step online.

$\sqrt{3t}=2$

Unlock this full step-by-step solution!

Learn how to solve equations with square roots problems step by step online. Solve the equation with radicals (3t)^0.5-2=0. We need to isolate the dependent variable t, we can do that by subtracting -2 from both sides of the equation. Removing the variable's exponent. Divide both sides of the equation by 3.

Final Answer

$t=\frac{4}{3}$

Problem Analysis

$\sqrt{3t}-2=0$

Time to solve it:

~ 0.03 seconds